Salivary duct carcinoma of the supraglottis with a distinct presentation: A case report and literature review. Issue 11 (March 2018) - Hsu, Cheng-Chieh; Li, Wing-Yin; Chu, Pen-Yuan
Abstract: Rationale: Salivary duct carcinoma (SDC) is a rare and aggressive subtype of salivary gland carcinoma that histologically resembles in situ and invasive ductal carcinoma of the breast. We present the first case of advanced SDC of the minor salivary gland arising from the supraglottis and review the literature on the clinicopathologic characteristics and prognosis of SDC. Patient concerns: A 59-year-old male patient with progressive difficulty in swallowing and a muffled voice for 2 months. Diagnoses: The patient was diagnosed with SDC arising from the supraglottis with extensive tumor invasion into the subsites of the larynx and pharynx. Interventions: Due to impending airway obstruction, the patient underwent CO2 laser debulking surgery. In addition to local disease, lymph node and distant metastases were also noted at diagnosis and concurrent chemoradiation therapy was arranged. Outcomes: Laryngeal function was preserved and tracheostomy was avoided. The patient has survived for >1 year after the initial diagnosis. Lessons: SDC is a rare and aggressive subtype of salivary gland carcinoma that histologically resembles in situ and invasive ductal carcinoma of the breast. Here we presented the first case of advanced SDC of the minor salivary gland arising from the supraglottis that was treated with CO2 laser debulking surgery followed by concurrent chemoradiation therapy. Due to their rarity, further studies are required to establish the most effective treatment protocol for advanced SDC.